Diseño de un manual de facilidades para turismo accesible y calidad turística en el cantón La Maná de la provincia de Cotopaxi, 2018 - Bermello Ponce, Gabriela Mishelle (2018)
The present investigation was aimed at to establish the guidelines to be followed by tourist sites in the La Maná canton province of Cotopaxi, through the elaboration of a facilities manual, focused on accessible tourism and tourist quality. The methods used were analytical, synthetic, and observation. The current situation of the study area was diagnosed, collecting primary and secondary information, according to the components biophysical-environmental, socio-cultural, economic-productive and tourism, in this way, were analyzed general aspects such as climatic variables, natural resources, population, tourist attractions, infrastructure and basic services. The needs of the offer were identified, taking into account 44 inventoried sites and 42 service providers, 6 potential attractions were selected, the same ones that presented poor facilities, as well as 12 tourist establishments, of which 7 evidenced greater accessibility and 4 receive tourists with disabilities and with some type of difficulty such as pregnant women or older adults. On the other hand, a market study was carried out, through 383 surveys applied in the cantons of La Maná, Pujilí, Valencia and Quevedo, the profile of the tourist was determined, which is in a range of 21 to 30 years, travels in the company of the family for one or two days on holidays, is informed through social networks and organizes trips on their own, 75% have at least one family member with physical or visual disabilities. Finally, the manual was designed based on the ecuadorian technical norms INEN, structured in four chapters that detail general considerations of accessible tourism, suggestions for the attention of the demand, accessibility guidelines to the physical environment and recommendations to establish quality standards. Keywords: Accessible tourism, standards INEN, tourist quality, disability